A common school base: analysing the National Curricular Common Base educational Project - Filipe, Fabiana Alvarenga [UNESP]; dos Santos Silva, Dayane [UNESP]; de Carvalho Costa, Áurea [UNESP] (FapUNIFESP (SciELO), 2021)
The aim of this article was to analyse the educational project proposed as the basis of the National Curricular Common Base (NCCB). To do this, a qualitative, documental research was carried out of the final version of NCCB, April 2017, approved on December 20, by the National Education Council. We observed that the NCCB is based on an educational training project for employability, using centrality of competencies, based on a directed Teaching model, prescriptive and linked to an efficiency evaluation model, inspired by behavioural theories. We concluded that NCCB proposals are removed from an educational Project aimed at a critical and emancipatory formation, because they propose to train for the work according to neoliberal demands.
Una base común en la escuela: análisis del proyecto educativo de la Base Nacional Común Curricular
Uma base comum na escola: análise do projeto educativo da Base Nacional Comum Curricular
Keywords: Curriculum Conceptions; National Curricular Common Base; Neoliberal Educational Project